Pengembangan Produk Melalui Strategi Pemasaran Produk Kopi Bubuk Dalam Meningkatkan Penjualan: - Rifka Fachrina; Muhammad Andre Alkahfi; Nita Erdina; Indry Anggraini Putri; Zainarti Zainarti (Transformasi Manageria: Journal of Islamic Education Management, 2023)
, Nita Erdina3, Marketing strategy is a strategy designed to promote goods or services with the aim of making a profit. The purpose of this study is to find out how product development through product marketing strategies through ground coffee product marketing strategies in increasing sales of gem coffee powder products. This research is descriptive qualitative, this method is used so that the writer knows or describes the reality of the event under study. Which is where the aim of the research was to find out how a good marketing strategy is for the development of sales of gem coffee products. The results of the study show that Permata Kopi does not maximize its marketing strategy. The newly optimized strategy is the product strategy. It is better if the owner of Permata Kopi is able to reconfirm his strategy, expand the marker network and increase promotions so that people are aware of Permata Kopi products. Keywords: coffee, marketing strategy, product